In-house validation for the determination of honey adulteration with plant sugars (C4) by Isotope Ratio Mass Spectrometry (IR-MS) - Cengiz, Mehmet Fatih; Durak, M. Zeki; Ozturk, Musa (ELSEVIER, 2014)
The objective of any analytical measurement is to obtain consistent, reliable, and accurate data. Validated analytical methods play a major role in achieving this goal. Although there have been many studies reporting about the isotopic compositions of honeys, little has been documented regarding the validation of these methods. In this study, an Isotope Ratio Mass Spectrometry (IR-MS) method for the determination of honey adulteration was validated in-house in terms of selectivity, stability, linearity, accuracy, repeatability, sensitivity, and recovery. This study was the first attempt to describe some important method validation parameters, such as the limit of detection CLOD), limit of quantification (LOQ), and recovery for the IR-MS studies. The LOD of the method was 0.11%, and the LOQ was 0.38% based on the percent adulteration ratio. The recovery value for spiked blank honey sample with the in-house standard was 98.57%. To evaluate the usefulness of the method 13 different brands of honey samples were collected from markets in Turkey and analyzed. The ranges of delta C-13 values of analyzed honey samples and their protein fractions were from -12.87 +/- 0.01 to 25.56 +/- 0.08 parts per thousand and from -23.77 +/- 0.09 to -25.98 +/- 0.06 parts per thousand, respectively. Adulteration was found in one honey sample. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Extraction; IR-MS; Isotopic analysis; Method validation; Optimization; FRUCTOSE CORN SYRUP; HPAEC-PAD; SAMPLES; CHROMATOGRAPHY; Food Science & Technology